The mask in Muzaffar al-Nawab's poetry (Journal of the College of Basic Education, 2026)
The mask is a new technique that has entered the realm of modern poetry, giving it one of its main characteristics within the process ofemploying symbols. The mask is part of the symbol, or rather, an aspect of the symbolic process. It is entirely possible for any elaborate mask to rise to the level and effectiveness of the symbol. Poets have resorted to the mask as an artistic means of expressing their experiences indirectly. It is a newly emerging technique in contemporary Arabic poetry. Its use has been widespread since the 1960s, influenced by Western poetry and its innovative techniques, to tone down the lyricism and directness of poetry. The poet imbues this character with his own features and borrows from theirs, creating a mask that is neither the character nor the poet, but rather the poet and the character together. This study aimed to uncover Muzaffar al-Nawab's use of this technique, the extent to which he benefited from it, the manner in which this benefit was reflected in his use of this technique, and the extent to which he employed it. In this study, the researcher identified and classified al-Nawab's important masks in his poetry